Are Sex Differences in Outcomes of Patients with ACS from Observational Registries Similar to the Findings from Randomized Clinical Trials? - P. Gale, Chris; Bebb, Owen (Current Pharmaceutical Design, 2016)
Background: The incidence of acute coronary syndrome is reported to be higher for males than females, yet clinical outcomes following acute myocardial infarction are worse among females. Information about acute coronary syndrome outcomes is obtained from randomised and cohort data. However, randomised controlled trials which are designed to evaluate the efficacy of clinical interventions often have limited external validity, and observational studies which draw inferences from the effect of an exposure whilst being more generalizable are limited by confounding. Methods: We undertook a structured literature review of research manuscripts published between 2000 and 2015 to examine whether reported sex-dependent outcomes following acute coronary syndrome differed between randomised control trials and observational registries. Results: Of 56 manuscripts, we found consistency between the two types of study designs – each type of study describing worse clinical outcomes for females with acute coronary syndrome. We also found a reduction in the use of guideline recommended therapy in females. Conclusion: Further research is needed to understand at a mechanistic and health services level why such a discrepancy in clinical outcomes exists.
Keywords: sex outcomes